An efficient sampling scheme for approximate processing of decision support queries - Rudra, Amit; Gopalan, Raj; Achuthan, Narasimaha (INSTICC, 2012)
Decision support queries usually involve accessing enormous amount of data requiring significant retrieval time. Faster retrieval of query results can often save precious time for the decision maker. Pre-computation of materialised views and sampling are two ways of achieving significant speed up. However, drawing random samples for queries on range restricted attributes has two problems: small random samples may miss relevant records and drawing larger samples from disk can be inefficient due to the large number of disk accesses required. In this paper, we propose an efficient indexing scheme for quickly drawing relevant samples for data warehouse queries as well as propose the concepts of database and sample relevancy ratios. We describe a method for estimating query results for range restricted queries using this index and experimentally evaluate the scheme using a relatively large real dataset. Further, we compute the confidence intervals for the estimates to investigate whether the results can be guaranteed to be within the desired level of confidence. Our experiments on data from a retail data warehouse show promising results. We also report the levels of accuracy achieved for various types of aggregate queries and relate them to the database relevancy ratios of the queries.